Page_40otherSonic Spectres: Word Ghosts in Madeleine Thien's Dogs at the Perimeter and the Digital Map Project, 'Fictional Montreal/Montréal fictif'. Issue 1 (14th November 2018) - Morgan, Ceri
Abstract : This article analyzes various ghosts and their connections with the unsaid and said in relation to Madeleine Thien's Dogs at the Perimeter (2011) and the digital map project, 'Fictional Montreal/Montréal fictif' (Morgan and Lichti, 2016–17). Drawing on Jacques Derrida's work on spectres, it suggests that Thien's novel offers both negative and positive hauntings, by drawing attention to the far-reaching effects of the Cambodian genocide. It goes on to reflect on absence and presence, voice and body in relation to the digital map, which features recordings of authors reading extracts of their fiction set in Montréal. Arguing that 'Fictional Montreal/Montréal fictif' performs an interplay between material and imaginary geographies, the article proposes that the map offers the possibility of new conceptualizations of Montréal. In so doing, it argues that both it and Dogs at the Perimeter embrace the potentially utopian aspect of spectrality identified by Derrida. This is due to their encouraging readers to think about our collective responsibilities to each other in a world characterized by mobility and migration.